(untitled) (Linguostylistic Studies, 2022)
This article comprehensively, with the involvement of lexical-grammatical and stylistic interpretation, analyzes expressions of debitive modality, selected from media texts of the early 21st century, emphasizes the communicative and pragmatic specialization of debitive constructions, and identifies the role thereof in realization of various communicative situations and manipulative strategies. The paper defines the status of debitive modality and characterizes it against the background of objectivity / subjectivity, reality / unreality / potentiality, morphological / syntactic / lexical-grammatical varieties. The language units that are basic in structuring the debitive expressions are identified, and a hierarchy of constructions, from the highest to the lowest degrees of obligation, has been determined. It allowed to distinguish four groups of syntactic units indicating: 1) inevitability (with predicates to be, (to be) condemned, (to be) doomed, (to be) inevitable, (to be) destined, etc. (бути, приречено, приречений, не минути, суджено, судилося та ін.)); 2) necessity (in the verbalization of this meaning the language units such as must, (to be) obliged, (to be) compelled, have to, need (to), should, ought to, duty, necessity, etc. (мусити, зобов’язаний, змушений, повинен, потрібно, необхідно, слід, варто, треба, обов’язок, необхідність тощо) are involved; 3) demand, coercion (the formal markers are the verbs to command, to demand, to force, to compel, to impose, to order (веліти, вимагати, заставляти, змусити, примусити, нав’язати, наказати, силувати)); 4) expediency, recommendation (with the words must, have to, should, ought to, need (to) (повинен, варто, слід, потрібно)). A commentary is given to clarify the emotional and expressive load of all the given types. The study argues that statements with a semantic connotation of inevitability prompt the reader to acknowledge themselves as the object of external influence and have different (positive, or more often, negative) psycho-emotional load. Partial leveling of compulsion is inherent in the structures of conditionality which inform about the factor prerequisite for a particular action. The structures with an indication of expediency and advisability represent actions related to conscious choice. The same modal plan, but in a combination with semantics of order, is characteristic of constructions with the meaning of necessity. The sentences with a modal connotation of necessity reflect urgent and non-categorical needs. Constructions with the meaning of coercion and demand usually cause internal resistance in the addressee and awareness of violations of their inner freedom.